Optimizing row spacing and plant population arrangement for a new short-height castor genotype in fall-winter - Souza-schlick, Genivaldo David De [UNESP]; Soratto, Rogério Peres [UNESP]; Zanotto, Maurício Dutra [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2014)
Plant population and arrangement should be properly designed to maximize the seed yield of short-height genotypes of castor (Ricinus communis L.) in each cropping season. Experiments were performed in the in the fall-winter cropping season of 2008 and 2009 in Botucatu, State of São Paulo, Brazil, to evaluate the effects of row spacing (0.45, 0.60, 0.75, and 0.90 m) and plant population (25,000, 40,000, 55,000, and 70,000 plants ha-1) on agronomical traits, yield components, seed yield, and oil yield of the genotype FCA-PB. A high plant density caused a reduction in plant survival and increased the first raceme insertion height, particularly in the year with the higher rainfall. The basal stem diameter, number of racemes per plant, and seeds per raceme were reduced by increasing the plant density. However, the seed and oil yields were minimally influenced by plant population density and row spacing because the castor plant compensated for a low plant population with a high number of racemes and seeds. The maximum seed yield was achieved with an estimated 0.64 m of row spacing and 50,107 plants ha-1 (i.e., 3.2 plants m-1).

Para maximizar a produtividade de grãos de genótipos de mamona (Ricinus communis L.) de porte baixo, devem ser definidos a população e o arranjo de plantas mais adequados a cada época de cultivo. Foi conduzido um experimento no outono-inverno dos anos de 2008 e 2009, em Botucatu-SP, para avaliar os efeitos do espaçamento entre fileiras (0,45; 0,60; 0,75 e 0,90 m) e da população de plantas (25.000, 40.000, 55.000 e 70.000 plantas ha-1) sobre as características agronômicas, componentes da produção, produtividade de grãos e de óleo do genótipo FCA-PB. Elevada densidade de plantas provocou redução na sobrevivência das mesmas e aumentou a altura de inserção do primeiro racemo, especialmente no ano com maior disponibilidade hídrica. O diâmetro do caule, o número de racemos por planta e de sementes por racemo foram reduzidos com o aumento da densidade de plantas. As produtividades de grãos e de óleo foram pouco influenciadas pela população de plantas e espaçamento entre fileiras, pois a mamoneira compensa um baixa população de plantas, com um elevado número de racemos e grãos por planta. A máxima produtividade de grãos foi obtida com o espaçamento entre fileiras estimado de 0,64 m e 50.107 plantas ha-1 (ou seja, 3,2 plantas m-1).
Combinação ótima de espaçamento e população de plantas para um novo genótipo de mamona de porte baixo na safrinha
Keywords: Ricinus communis; distribuição especial de plantas; densidade de plantas; produtividade de grãos; teor de óleo; Ricinus communis; spatial plant distribution; plant density; grain yield; oil content